2017
DOI: 10.4103/0366-6999.209884
|View full text |Cite
|
Sign up to set email alerts
|

Variants in the Promoter Region of HLA-DQA1 were Associated with Idiopathic Membranous Nephropathy in a Chinese Han Population

Abstract: Background:Idiopathic membranous nephropathy (IMN) is an autoimmune disease and the leading cause of adult nephritic syndrome. HLA-DQA1 had been identified to be associated with IMN in Europeans and the result was replicated in Chinese Han population. In this study, six single nucleotide polymorphisms (SNPs) in the promoter of HLA-DQA1 and other two SNPs with IgA nephropathy were included for the association analysis.Methods:The SNPs were genotyped in 509 patients and 601 controls by the MassArray iPLEX. The q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Overall, 27 studies with a total of 5353 PMN cases and 10,777 controls were included in the present study. 13 – 35 The characteristics of included studies are summarized in Table 1 . Genotyping data of cases and controls are depicted in Supplemental Tables S1–S10 .…”
Section: Resultsmentioning
confidence: 99%
“…Overall, 27 studies with a total of 5353 PMN cases and 10,777 controls were included in the present study. 13 – 35 The characteristics of included studies are summarized in Table 1 . Genotyping data of cases and controls are depicted in Supplemental Tables S1–S10 .…”
Section: Resultsmentioning
confidence: 99%
“…The HLA-DQA1 allele on chromosome 6p21 is closely related to IMN, mainly in Caucasian populations, and this allele may promote autoimmune responses to targets, which include PLA2R1 variants. [ 32 ] HLA-DQA1 rs2187668 is known to be associated with IMN, and carriers of the major allele of HLA-DQA1 rs2187668 have a higher probability of harboring PLA2R1 rs4664308 major allele to increase the IMN risk. However, studies have shown Asians are less likely to exhibit PLA2R1 genetic variations to increase IMN risk.…”
Section: Discussionmentioning
confidence: 99%